Therapeutic Drug Monitoring (TDM) in The Use of Aspirin as Antirheumatoid Drugs - Miladiyah, Isnatin (Sains Medika: Jurnal Kedokteran dan Kesehatan, 2012)
Therapeutic drug monitoring (TDM) is used in drug therapy for selected drugs with narrow therapeutic index, or a broad range of kinetics variation, or drugs with strong correlation between plasma concentration and clinical effects or toxicity. Aspirin is one of the widely used old generation drugs, with a broad range of activity spectrum: analgesic, antipyretic, antiÃ¢â‚¬Âinflammatory, and antiplatelet. As antiÃ¢â‚¬Âinflammatory drug, aspirin directed as therapy for many of chronic inflammation, such as rheumatoid arthritis. As an antirheumatic agent, aspirin shows a wide variation in the pharmacokinetic of aspirin metabolism, and has a narrow therapeutic index because it effectives at concentration of 10Ã¢â‚¬Â30 mg/dl, but at more than 40 mg/dl intoxication occurs (metabolic acidosis, hyperpnea, and death). Those are why aspirin use as antirheumatic agent need therapeutic drug monitoring, so that doctors can guarantee that plasma aspirin concentration is in the therapeutic range, to achieve optimilization of therapy with minimal side effects. This article reveals about use of aspirin as antirheumatoid drugs and why therapeutic drug monitoring is needed in aspirin use (Sains Medika, 4(2):210Ã¢â‚¬Â226).